The balance of type 1 and type 2 immune responses in the contexts of hepatitis B infection and hepatitis D infection - Townsend, Elizabeth C; Zhang, Grace Y; Ali, Rabab; Firke, Marian; Moon, Mi Sun; Han, Ma Ai Thanda; Fram, Benjamin; Glenn, Jeffrey S; Kleiner, David E; Koh, Christopher; Heller, Theo (Journal of gastroenterology and hepatology, 2019)
Background and Aim Hepatitis delta virus (HDV) infection is the most rapidly progressive chronic viral hepatitis. Little is understood about the immune responses to HDV. This study aims to characterize the systemic immune environments of hepatitis B virus (HBV) and HDV patients at various disease stages. Methods A total of 129 subjects were evaluated: 53 HBV, 43 HDV, and 33 healthy controls. HBV and HDV subjects were categorized by aspartate aminotransferase to platelet ratio index (APRI) into mild (APRI < 0.5), moderate, and severe (APRI > 1.0). Serum cytokines and immune markers were assessed at a single treatment‐naïve time‐point. Results Type 1 cytokines are elevated in both HBV and HDV. Both groups show higher tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐12p40, and C–X–C motif chemokine ligand 9 when compared with controls (all P < 0.05). However, only HBV group displayed elevated γ‐interferon compared with controls. Type 2 cytokines are elevated in HBV. HBV group shows higher IL‐4, IL‐13, and C–C motif chemokine ligand (CCL) 26 compared with healthy controls and HDV. Chemokines CCL2 and CCL13 are lower in HDV. When assessing ratios, HDV displays higher γ‐interferon/IL‐4, TNF‐α/IL‐4, and TNF‐α/IL‐13 ratios than HBV and controls. Conclusion Hepatitis B virus and HDV subjects show similarly elevated type 1 cytokines. HDV subjects display relatively lower type 2 cytokines. These differences in the systemic immune environments, particularly the predominance of type 1 responses, may contribute to the comparatively rapid progression of HDV disease. Characterization of the imbalance in type 1 and type 2 immunity unique HDV has the potential to provide immunological insights for designing therapeutic targets in HDV‐associated disease progression.